Pelatihan Penyusunan Anggaran Produksi Usaha “Kedai Kopi Toraja Randan Uma” di Tongkonan Lempe Kabupaten Toraja Utara - Westerini Lusdani; Rati Pundissing; Dwibin Kannapadang; Ade Lisa Matasik; Randi Tangdialla (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Business development in Indonesia continues to experience growth. In order for a business to be able to compete in this very complex era of industrial revolution 4.0, it needs to be supported by basic skills in better business planning, one of which is the coffee shop business. This service activity is to provide training regarding the importance of making a simple production cost budget, and the method of implementing this activity is to provide training, discussions and questions and answers and participants are very enthusiastic about participating in the training. The aim of this service is to increase participants' knowledge of the importance of preparing a production budget as a tool for planning and controlling costs in making business decisions, as well as to increase the participants' ability to prepare production budgets so that the mandate given to them as business actors can be properly accounted for. This is due to a lack of understanding by business actors. This is due to a lack of understanding by business actors about the importance of preparing a production budget as a basis for making decisions on business management, as well as a lack of understanding about how to calculate a production budget properly and correctly. Based on the results of the service, it can be seen that the training activity participants really understood the explanation of the material presented. This was proven by the various questions asked and discussions, and the participants were able to solve the cases given.